) 40+6 1/9:2 1/17-10/11=42,1
6 1/9:2 1/17=55/9:35/17=55×17:9×35=187/63=
=2 61/63
40 + 2 61/63=42 61/63
42 61/63-10/11= 42 (671-630/693)=
42 41/693=42,1
2. 53,5-14 1/6×1 1/17+8 2/3=29 5/6
14 1/6×1 1/17=85/6×18/17=15
53,5-15=38,5 =38 1/2
38 1/2- 8 2/3= 30 (1/2-2/3)=30 (3-4/6)=
=30 (-1/6)= 29 6/6-1/6=29 5/6
3. 4 5/8:3 1/12+14, 5-9 7/9=6 2/9
4 5/8:3 1/12=36/8:37/12=36×12:8×37=
=54/37=1 17/37
1 17/37+14,5=1,5+14,5=16
16-9 7/9= 15 9/9-9 7/9=6 2/9
4. 10 1/6+2 3/21×14/47-3,2=7,6
2 2/21×14/47=44/21×14/47=88/141 =0,6
10 1/6+0,6=10,2+0,6=10, 8
10,8 -3,2=7,6
1)
{2x+7 >1
{x - 3<1
{2x > 1 - 7
{x < 1 + 3
{x > (- 6)/2
{x < 4
{ x> - 3
{ x< 4
x∈ (-3;4)
2)
{3y<21
{4-y>0
{y < 21/3
{4 > y
{y<7
{y< 4
y∈(-∞,4 )
3)
{4х +9 > -15
{2-x<5
{4x> -15 -9
{2-5 < x
{4x > -24
{x >-3
{x>-24/4
{x>-3
{x>-6
{x>-3
x∈(-3; ∞ )
4)
{2x+3>x-1
{5x-22<x+2
{2x -x > -1-3
{5x-x< 2+22
{x>-4
{4x<24
{x>-4
{x<6
x∈(-4 , 6 )
5)
{7x+9<2x-1
{4+11x>9x-14
{7x-2x<-1-9
{11x-9x>-14-4
{5x<-10
{2x> - 18
{x<-2
{x> - 9
x∈ (-9, - 2)
6)
{x>0
{x-5>2x+1 ⇒ -5-1>2x-x
{x>0
{x< -6
х ∈ ∅ нет решении